Fundamental Properties of a Large, Unbiased Sample of Massive, Young, Embedded Star Clusters in the Milky Way. Issue Volume 12:Issue S316(2015) (31st March 2017) - Dallilar, Yigit; Barnes, Peter; Lada, Elizabeth; Ryder, Stuart
Abstract: In this project, we focus on the analysis of infrared observations of the clumps defined with the Galactic Census of High- and Medium-mass Protostars (ChaMP) (Barnes et al. 2011 ). We derive line of sight infrared extinction values, star counts and protostar candidates around the molecular gas emission obtained with the Mopra telescope. Then, we examine the correlation between radio and infrared properties of the clumps. For this stage of the project, we use the Vela-Carina and 2MASS catalogs to obtain a preliminary understanding of the final results. For the later stages, we will extract infrared photometry from our deep AAT near-IR and Spitzer 3.6 and 4.5 μm images. With the final deep photometry results, we will compile the properties of individual clusters.